1990
DOI: 10.1152/ajprenal.1990.258.3.f606
|View full text |Cite
|
Sign up to set email alerts
|

Role of the kidney in primary hypertension: a renal transplantation study in rats

Abstract: We have previously shown that transplantation of kidneys from genetically hypertensive to normotensive rats result in hypertension in renal graft recipients. To investigate whether this posttransplantation hypertension may have been the result of damage to the renal graft by high perfusion pressure before transplantation, we normalized blood pressure throughout life in spontaneously hypertensive rat (SHR) kidney donors by continuous antihypertensive treatment with the angiotensin-converting enzyme inhibitor ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
66
0
4

Year Published

1991
1991
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(73 citation statements)
references
References 0 publications
3
66
0
4
Order By: Relevance
“…Hypertension is transferred to WKY rats by transplantation of SHR kidneys and vice versa. 19 In addition, a number of abnormalities in renal function, which normalize as blood pressure increases, are observed in young SHR, indicating that an elevated blood pressure may be necessary to compensate for the decreased renal function in SHR. 20 The exact nature of the renal defect is not clear, but there is evidence to suggest that the RAS could be involved.…”
Section: Plasma Renln Concentrationmentioning
confidence: 99%
“…Hypertension is transferred to WKY rats by transplantation of SHR kidneys and vice versa. 19 In addition, a number of abnormalities in renal function, which normalize as blood pressure increases, are observed in young SHR, indicating that an elevated blood pressure may be necessary to compensate for the decreased renal function in SHR. 20 The exact nature of the renal defect is not clear, but there is evidence to suggest that the RAS could be involved.…”
Section: Plasma Renln Concentrationmentioning
confidence: 99%
“…One criticism of the transplantation studies is that SHR renal grafts may have been damaged secondary to the increased renal perfusion pressure of these animals before transplantation. This objection was addressed by studies in which SHR kidneys were protected from elevated pressure by long-term antihypertensive treatment before transplantation, 37 or renal grafts were obtained from young (4-week-old) SHR that were presumably prehypertensive. 36 In both cases, normotensive recipients of SHR renal grafts developed hypertension, and recipients of WKY rat renal grafts did not.…”
mentioning
confidence: 99%
“…4 Thus, hyperuricemia may reflect the primary role of the kidney in the pathogenesis of hypertension. 5 It has been suggested that hyperuricemia may represent an additional risk factor for the development of cardiovascular disease. 6 Excessive oxidant stress may be instrumental in the onset and maintenance of experimental hyperten-sion.…”
mentioning
confidence: 99%